Active Template Synthesis of Protein Heterocatenanes. Issue 32 (12th July 2019) - Da, Xiao‐Di; Zhang, Wen‐Bin
Abstract: Covalent‐bond‐forming protein domains can be versatile tools for creating unconventional protein topologies. In this study, through rewiring the SpyTag–SpyCatcher complex to induce rationally designed chain entanglement, we developed a biologically enabled active template for the concise, modular, and programmable synthesis of protein heterocatenanes both in vitro and in vivo. It is a general and good‐yielding reaction for forming heterocatenanes with precisely controlled ring sizes and broad structural diversity. More importantly, such heterocatenation not only provides an efficient means of bioconjugation for integrating multiple native functions, but also enhances the stability of the component proteins against proteolytic digestion, thermal unfolding, and freeze/thaw‐induced mechanical denaturation, thus opening up a versatile path in the nascent field of protein‐topology engineering. Abstract : Tie up loose ends : Protein‐heterocatenane formation was achieved using an active template developed by rewiring the connectivity of the SpyTag–SpyCatcher complex. Protein heterocatenanes are more resistant to proteolytic cleavage, thermal unfolding, and freeze–thawing than the individual, component proteins. This genetically encodable method provides a powerful way to integrate multiple proteins in one complex beyond simple fusion.